2008
DOI: 10.1086/522133
|View full text |Cite
|
Sign up to set email alerts
|

Varicella Vaccination of Immunocompromised Children

Abstract: Vaccination before immune compromise is often successful, and the vaccine-induced response is usually partially or fully protective. In many treatment settings, it is possible to safely vaccinate once the level of immune suppression has been reduced. Targets for future research are outlined. A consensus conference should be undertaken to develop guidelines for the use of varicella vaccine in immunocompromised children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 43 publications
(39 reference statements)
1
16
0
3
Order By: Relevance
“…In this study 9% (4/42) were found to not have a history of clinical infection or immunization against varicella placing them at risk, similar to the 10% found in the United States IBD survey[22]. The morbidity of varicella in immunosuppressed patients has led to studies challenging the general recommendation that this live attenuated vaccines not be administered[41]. A case series of six young people with IBD safely receiving varicella vaccination whilst on infliximab therapy[42].…”
Section: Discussionsupporting
confidence: 59%
“…In this study 9% (4/42) were found to not have a history of clinical infection or immunization against varicella placing them at risk, similar to the 10% found in the United States IBD survey[22]. The morbidity of varicella in immunosuppressed patients has led to studies challenging the general recommendation that this live attenuated vaccines not be administered[41]. A case series of six young people with IBD safely receiving varicella vaccination whilst on infliximab therapy[42].…”
Section: Discussionsupporting
confidence: 59%
“…[16,29] Limiting vaccination to immune-compromised patients is not feasible, since the current vaccine contains live-attenuated VZV, which may replicate unchecked and disseminate in severely immunecompromised children. [30,31] Vaccination of close contacts of immune-compromised children, such as varicella-susceptible siblings, could be a practical strategy. The benefi t of administering the live varicella vaccine to potential contacts of immune-compromised patients far outweighs any theoretical risks of transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Seroconversion rate and the effectiveness of more than 98% was observed in immunocompetent vaccine recipients after 2 doses of varicella vaccine [9]. Data from other immunocompromised populations including those with leukemia, chronic renal failure or chronic hepatic disease show seroconversion rate in a range of 85-100% [10].…”
Section: Discussionmentioning
confidence: 98%